(untitled) (London, 1995)
This book reviews the state of the art in information technolgy in educational management (ITEM) with emphasis on research, approaches, methodologies, applications and tools. This IFIP (International Federation of Information Processing) Proceedings not only discusses the pedagogical and educational issues in ITEM but also covers the range of applications from class scheduling to financial support.
Keywords: Information resources management,Information technology